More on the boundaries of the Vilniškiai subdialect of Eastern Aukštaitija - Kardelis, Vytautas (Lietuvių kalba, 2013)
The article deals with the question of the boundary of the Vilniškiai subdialect of Eastern Aukštaitija and addresses the problematic issues of its borders and area. On the basis of data accumulated during dialectal expeditions, the article thoroughly examines the boundary between the Vilniškiai and the Uteniškiai subdialects of Eastern Aukštaitija. The research has revealed that the boundary drawn between the Vilniškiai and the Uteniškiai subdielects of Eastern Aukštaitija as presented in dialectological literature to this date is not accurate. The article provides a more exact account of the borders between the two subdialects and draws the boundary between them in the map attached. The key conclusions of the article are as follows:a)    It is necessary to thoroughly research the boundaries between the Vilniškiai subdialect of Eastern Aukštaitija and the Širvintiškiai subdialect of Southern Aukštaitija and Eastern Aukštaitija and to examine the territory in the regions of Kernavė (540), Akmena (524), Troškūnai (525), Sužionys and Skirlėnai.b)    The boundary between the Vilniškiai and the Uteniškiai subdialects of Eastern Aukštaitija (starting with Lakaja) should be drawn as illustrated in the map attached.c)    In comparison to the area that is marked in the “Lietuvių kalbos atlasas” and “Lietuvių kalbos tarmių chrestomatyija” maps, the contemporary subdialect of Vilniškiai should exclude not only the district of Vilnius and the region of Pabradė but also the very North-eastern part situated between Visaginas, Liaudėnai, Tilžė, Turmantas and Smalvai. Separate marking should be carried out on the region of Dieveniškės, i.e. it should me marked as a mixed area.d)    The specification of the boundary of the Vilniškiai subdialect is important for the research of the interaction of dialects as well as the relationship between and dynamics of subdialects and Slavic language variations. If a comprehensive study of the language of all the generations was carried out, perhaps the dynamics of the boundaries of the subdialect would also be slightly different. In this regard as well as taking into account conclusions a) and b), the specified boundaries of the Vilniškiai subdialect of Eastern Aukštaitija should nevertheless be considered preliminary.
Keywords: none